PENGARUH PROPORSI SUKROSA DAN ISOMALT TERHADAP SIFAT FISIKOKIMIA DAN ORGANOLEPTIK SOFT CANDY SUSU KEDELAI - Sutedjo, Vonny Indra; Kusumawati, Netty; Widyawati, Paini Sri (Widya Mandala Surabaya Catholic University, 2015)
Soft candy is a kind of cotton candy which has a chewy and soft texture that has approximately 6-8% of water content. In this study, soy milk soft candies were made with isomalt as the replacement of sucrose that affected the physicochemical and organoleptic properties of soy milk soft candies. The design of the study was RGD (Randomized Block Design) single factor, namely the proportion of sucrose and isomalt. The proportion of sucrose and isomalt consisted of six level which are 75:25, 60:40, 45:55, 30:70, 15:85, and 0:100%(b/b)) with four replications. The parameters affected physicochemical properties (moisture content, reducing sugar levels, and texture) and the organoleptic properties preferences for taste, texture, and ease bitten). From the weighting test, it was found that the best treaement was P4 (sucrose : isomalt =30:70% (b/b)) with score of 7,52% for water content, 8,2322% of reducing sugar, hardness of 573,038 g.sec, adhesiveness of -74,644 g.sec, 4,7 for preference of taste (rather like), 4,9875 (rather like) for stickiness, and 4,2625 for chewiness (neutral).